Examining emergent niche sports' YouTube exposure through the lens of the psychological continuum model. (1st January 2013) - Mahoney, Tara Q.; Hambrick, Marion E.; Svensson, Per G.; Zimmerman, Matthew H.
The Funk and James (2001, 2006) psychological continuum model (PCM) suggests that sport consumers move from awareness and attraction to attachment and allegiance, and that most sport consumers first learn about sports via reference groups and the media. However, niche sports typically receive less media coverage than mainstream sports (Greenhalgh et al., 2011; Puchan, 2004). These sports must thus seek other avenues of promotion, including the internet and social media, to attract and retain consumers. This study explored the promotional use of online video aggregation site YouTube among five emergent niche sports – slacklining, adventure racing, longboarding, cyclocross and parkour – using the PCM as the theoretical framework. The majority of videos were categorised as awareness and attraction. The findings of this study showed the importance of online videos among niche sport organisations as a tool for providing information about their sports while building and cultivating relationships with consumers.